2020
DOI: 10.1155/2020/8855423
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics Study for Raloxifene in Postmenopausal Female with Osteoporosis

Abstract: Osteoporosis is characterized by decreased bone mineral density and increased risk of fracture. Raloxifene is one of the treatments of osteoporosis. However, the responses were variable among patients. Previous studies revealed that the genetic variants are involved in the regulation of treatment outcomes. To date, studies that evaluate the influence of genes across all genome on the raloxifene treatment response are still limited. In this study, a total of 41 postmenopausal osteoporosis patients under regular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
4
0
1
Order By: Relevance
“…19 Some studies suggest that raloxifene is capable of stimulating estrogenic pathways exclusively through ER β , justifying its tissue selectivity. 9,20,21 Our results showed that its isolated action was beneficial to the bone; however, as already described, the association with estrogen did not present an adjuvant effect. This result can be explained by competition for the receptor, or by inhibition of the estrogen receptor with this hormonal combination.…”
Section: Discussionsupporting
confidence: 74%
“…19 Some studies suggest that raloxifene is capable of stimulating estrogenic pathways exclusively through ER β , justifying its tissue selectivity. 9,20,21 Our results showed that its isolated action was beneficial to the bone; however, as already described, the association with estrogen did not present an adjuvant effect. This result can be explained by competition for the receptor, or by inhibition of the estrogen receptor with this hormonal combination.…”
Section: Discussionsupporting
confidence: 74%
“…Pharmacogenetics of BPs has focused on their rare but severe adverse event, the osteonecrosis of the jaw, in order to define patients prone to this effect (Guo et al, 2020). Pharmacogenomics of raloxifene (Lu et al, 2020) has also been studied in 41 postmenopausal OP patients under regular raloxifene treatment, and the genetic association with the bone mineral density response to raloxifene at the lumbar spine or femoral neck site has been characterized. Several genes have been identified to influence the bone response to raloxifene.…”
Section: Discussionmentioning
confidence: 99%
“…However, their efficacy is unsatisfactory ( Tu et al, 2018 ). Raloxifene is a selective estrogen receptor modulator that increases the risk of blood clots and stroke ( Lu et al, 2020 ). Meanwhile, hormone replacement therapy (HRP) is only recommended for postmenopausal women ( Gosset et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%